Kinematic Analysis of SNR3-C30 Robotic Arm based on Matlab - Tang, Qia (International Journal of Mechanical and Electrical Engineering, 2025)
With the continuous advancement of industrial automation, robotic arms have been widely adopted across various fields, making performance optimization a key research focus. As a critical component for enhancing robotic arm performance, kinematic analysis plays a vital role in achieving precise control. This study utilizes the MatlabRobotics toolbox to conduct kinematic analysis on the SNR3-C30 robotic arm. By establishing a mathematical model of the robotic arm and solving forward/reverse kinematic equations, we implemented a fifth-order polynomial interpolation algorithm for trajectory planning in the joint space. The research demonstrates that the established model accurately describes the robotic arm’s motion characteristics, while the forward/reverse kinematic solution method proves effective and reliable. These findings provide crucial theoretical foundations for optimizing design and developing control strategies for the SNR3-C30 robotic arm, significantly improving operational precision and efficiency in real-world applications. This work holds great significance for advancing robotic arm technology development.